Frecuencia de lesiones gástricas halladas post mortem en cerdos en la ciudad de Medellín (Colombia) - Rodriguez, Bernardo J.; Aranzazu, Diego; Valencia, Francisco; Franco, Oscar I.; Ortiz, Laura C. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary In this study the macroscopic inspection of 900 stomachs from pigs slaughtered in an abattoir at Medellin (Colombia) were performed, with the aim to determine the frequency of gastric injuries. Sample size calculation was made on the basis of an infinite population with a 99.7% confidence interval and a 5% alpha error. The results were analyzed by descriptive statistic and differences between proportions were established by a Z test. The prevalence of gastric ulcer was 34.88% (314/900), the pars oesophagea being the more affected region. Other highly frequent injuries included: hyperkeratosis 74.77% (673/900), epithelial erosion 46.50% (419/900), congestion 8.44% (76/900) and non ulcerative hemorrhage 4.22% (38/900). The geographic region precedence of the pigs with the greater presentation of ulcer was the eastern Antioquia State region. This article discusses the epidemiology and factors associated to genesis of gastric ulcer in pigs.